2019
DOI: 10.1016/j.ijrobp.2019.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Remission and Tumor-Infiltrating Lymphocytes During Chemoradiation Therapy: Predictive and Prognostic Markers in Locally Advanced Esophageal Squamous Cell Carcinoma

Abstract: In this study designed for patients with locally advanced esophageal squamous cell carcinoma using cases with excellent tumor remission and lymphocyte-predominant Purpose: Clinical tools are unavailable for accurate prediction of pathologic responses to chemoradiation therapy (CRT) among patients with esophageal squamous cell carcinoma (ESCC) before surgery. We evaluated tumor remission and tumor-infiltrating lymphocytes (TILs) during CRT as predictors of pathologic response and prognostic markers for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Although no study has identified tumor immune categories in EC, it has been reported that a high density of CD8 cells was significantly correlated with more favorable OS and RFS in patients who received post-CRT (18). Similarly, we found that high levels of TILs induced by CCRT were associated with improved clinical response and survival (19). Furthermore, the effect of intratumoral location of TILs on the survival of ESCC patients varies.…”
Section: Icis Required For Escc Treatmentsupporting
confidence: 50%
“…Although no study has identified tumor immune categories in EC, it has been reported that a high density of CD8 cells was significantly correlated with more favorable OS and RFS in patients who received post-CRT (18). Similarly, we found that high levels of TILs induced by CCRT were associated with improved clinical response and survival (19). Furthermore, the effect of intratumoral location of TILs on the survival of ESCC patients varies.…”
Section: Icis Required For Escc Treatmentsupporting
confidence: 50%
“…Outcome measures included objective response rate, overall survival (OS), and progression-free survival (PFS). A major pathological response was defined as <10% viable residual tumor cells 22 on a deep biopsy collected from the tumor primary site where residual tumor cells were most likely located guided by the endoscopic ultrasound image after 40 Gy radiation.…”
Section: Study End Pointsmentioning
confidence: 99%
“…Dynamic efficacy predictors during cancer treatment were important areas of exploration. Some studies confirmed that high levels of tumor-infiltrating lymphocytes were associated with better survival in patients with ESCC (31,32). Furthermore, several reports indicated that the efficacy of PD-1 inhibitors might be related to peripheral blood lymphocytes.…”
Section: Discussionmentioning
confidence: 91%